Valores óptimos de punto de corte de circunferencia abdominal para predecir alteraciones cardiometabólicas en una muestra representativa nacional de Venezuela. El estudio EVESCAM - González-Rivas, Juan P; Mechanick, Jeffrey I; Iglesias-Fortes, Rocio; De-Oliveira-Gomes, Diana; Silva, Jesús; Valencia, José; Figueroa, Estherbany; Duran, Maritza; Ugel, Eunice; Infante-García, María M; Marulanda, María Inés; Nieto-Martínez, Ramfis (Archivos de cardiologia de Mexico, 2020)
OBJECTIVE:: Waist circumference (WC) value reflects abdominal adiposity, but the amount abdominal fat that is associated to cardiometabolic risk factors varies among ethnicities. Determination of metabolic abnormalities has not undergone a WC adaptation process in Venezuela. The aim of the study was (1) to determine the optimal WC cutoff value associated with ≥2 cardiometabolic alterations and (2) incorporating this new WC cutoff, to determine the prevalence of abdominal obesity and cardiometabolic risk factors related in Venezuela. METHODS:: The study was national population-based, cross-sectional, and randomized sample, from 2014 to 2017. To assess performance of WC for identifying cardiometabolic alterations, receiver operating characteristics curves, area under the curve (AUC), sensitivity, specificity, and positive likelihood ratios were calculated. RESULTS:: Three thousand three hundred eighty-seven adults were evaluated with mean age of 41.2 ± 15.8 years. Using the best tradeoff between sensitivity and specificity, WC cutoffs of 90 cm in men (sensitivity = 72.4% and specificity = 66.1%) and 86 cm in women (sensitivity = 76.2% and specificity = 61.4%) were optimal for aggregation of ≥2 cardiometabolic alterations. AUC was 0.75 in men and 0.73 in women using these new cutoffs. Prevalence of abdominal obesity and metabolic syndrome was 59.6% (95 CI; 57.5-61.7) and 47.6% (95 CI; 45.2-50.0), respectively. Cardiometabolic risk factors were associated with being men, higher age, adiposity, and living in northern or western regions. CONCLUSION:: The optimal WC values associated with cardiometabolic alterations were 90 cm in men and 86 cm in women. More than half of the Venezuelan population had abdominal obesity incorporating this new WC cutoff.
Keywords: Metabolic syndrome; Venezuela; Abdominal obesity; Adiposity; Waist circumference